Gender differences in intra-household financial decision-making: An application of coarsened exact matching - Frederik Booysen; Sevias Guvuriro (Journal of Risk and Financial Management, 2021)
Most studies that explore collective models of intra-household decision-making use economic outcomes such as human capital, earnings, assets, and relative income shares as proxies of the relative distribution of bargaining power. These studies, however, fail to incorporate important measures of control over and management of the economic resources within households. In the current study, a direct measure of financial decision-making power within the household is used to directly assess the distribution of bargaining power. Coarsened exact matching, an identification strategy not yet applied in studies of this nature, is applied to couple-level observational data from South Africa's longitudinal National Income Dynamics Study. The influence of gender differences in intra-household decision-making on resource allocations to per capita household expenditure is assessed. In the case of greater financial decision-making power in couples being assigned to wives rather than husbands, per capita household expenditure on education increases significantly. The empowerment of women with financial decision-making power therefore holds the promise of realizing the benefits of investments in human capital.
Keywords: 330; coarsened exact matching; gender; household expenditure; intra-household decision-making; resource allocation; South Africa